The paradox of NKp46+ natural killer cells: drivers of severe hepatitis C virus-induced pathology but in-vivo resistance to interferon α treatment. Issue 3 (11th May 2013) - Pembroke, Tom; Christian, Adam; Jones, Emma; Hills, Robert K; Wang, Eddie C Y; Gallimore, Awen M; Godkin, Andrew
Abstract : Objective: There is evidence that natural killer (NK) cells help control persistent viral infections including hepatitis C virus (HCV). The phenotype and function of blood and intrahepatic NK cells, in steady state and after interferon (IFN) α treatment has not been fully elucidated. Design: We performed a comparison of NK cells derived from blood and intrahepatic compartments in multiple paired samples from patients with a variety of chronic liver diseases. Furthermore, we obtained serial paired samples from an average of five time points in HCV patients treated with IFNα. Results: Liver NK cells demonstrate a distinct activated phenotype compared to blood manifested as downregulation of the NK cell activation receptors CD16, NKG2D, and NKp30; with increased spontaneous degranulation and IFN production. In contrast, NKp46 expression was not downregulated. Indeed, NKp46-rich NK populations were the most activated, correlating closely with the severity of liver inflammation. Following initiation of IFNα treatment there was a significant increase in the proportion of intrahepatic NK cells at days 1 and 3. NKp46-rich NK populations demonstrated no reserve activation capacity with IFNα treatment and were associated with poor viral control on treatment and treatment failure. Conclusions: NKp46 marks out pathologically activated NK cells, which may result from a loss of homeostatic control of activating receptor expression in HCV. Paradoxically these pathological NK cells do not appear to be involved in viral control in IFNα-treated individuals and, indeed, predict slower rates of viral clearance.